Association between autoimmune diseases and myelodysplastic syndrome:a Mendelian randomization study - Zhengyang Miao; Wenwei Zhu; Yongming Zhou; Hailin Chen (Hematology)
Background: The relationship between different types of autoimmune diseases and myelodysplastic syndrome (MDS) is inconclusive. Therefore, we employed Mendelian randomization (MR) to examine whether genetically predicted susceptibility to ten autoimmune diseases is associated with the risk of MDS.Methods: Single nucleotide polymorphisms (SNPs) significantly associated with 10 autoimmune diseases were extracted from the summary statistics of European genome-wide association studies (GWAS). A two-sample MR analysis was performed using summary-level statistics sourced from GWAS datasets. Inverse-variance weighting (IVW), MR–Egger, and weighted median (WM) were further supported by several sensitivity analyses.Results: Four autoimmune diseases showed genetical predisposition to MDS: rheumatoid arthritis (OR = 1.186,95% CI = 1.028-1.367, P = 0.019), multiple sclerosis (OR = 1.247, 95% CI = 1.013-1.534, P = 0.037), myasthenia gravis (OR = 1.326,95% CI = 1.010-1.742, P = 0.042), and Hashimoto thyroiditis(OR = 1.519,95% CI = 1.008-2.290, P = 0.046). Nevertheless, no similar causal relationship was found between the remaining seven autoimmune diseases and MDS. The accuracy and robustness of these findings were confirmed by sensitivity tests.Conclusions: We are the first to use MR analysis to explore the relationship between autoimmune diseases and MDS. The mechanism needs to be further explored.